2020
DOI: 10.1073/pnas.1918335117
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the origins of confidence in speeded perceptual judgments through multimodal imaging

Abstract: The human capacity to compute the likelihood that a decision is correct—known as metacognition—has proven difficult to study in isolation as it usually cooccurs with decision making. Here, we isolated postdecisional from decisional contributions to metacognition by analyzing neural correlates of confidence with multimodal imaging. Healthy volunteers reported their confidence in the accuracy of decisions they made or decisions they observed. We found better metacognitive performance for committed vs. observed d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
60
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 77 publications
15
60
1
Order By: Relevance
“…Previous studies supporting this thesis have shown that one's own motor response that precedes confidence judgment increases correlations between confidence and response accuracy (Pereira et al, 2018;Siedlecka et al, 2016;Siedlecka et al, 2019b;Wierzchoń et al, 2014;Wokke et al, 2019). However, in a recent study, Filevich and colleagues (Filevich et al, 2019) found that when participants were asked to continuously track decision-related characteristics of stimuli (the motion direction of the stimulus) by pressing the left and right keys, their confidence in a temporalsummation decision task was higher than in the no-tracking condition.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies supporting this thesis have shown that one's own motor response that precedes confidence judgment increases correlations between confidence and response accuracy (Pereira et al, 2018;Siedlecka et al, 2016;Siedlecka et al, 2019b;Wierzchoń et al, 2014;Wokke et al, 2019). However, in a recent study, Filevich and colleagues (Filevich et al, 2019) found that when participants were asked to continuously track decision-related characteristics of stimuli (the motion direction of the stimulus) by pressing the left and right keys, their confidence in a temporalsummation decision task was higher than in the no-tracking condition.…”
Section: Discussionmentioning
confidence: 92%
“…First, the possibility that this decrease in metacognitive performance derived from differences at the perceptual level was excluded by equating first-order performance across conditions, and by re-analysing confidence judgments with a signal detection theory approach which accounts for potential differences in first-order performance (Maniscalco & Lau, 2012). Of note, this approach assumes that confidence estimates are computed based on the same evidence as the perceptual task, while the mixed effects logistic regression approach assumes that confidence can be based both on decisional and post-decisional cues (see Pereira et al, 2018 for recent results disentangling decisional and post-decisional contributions to confidence). As metacognitive impairments were found relying on signal detection theory and mixed logistic regression approaches, we cannot determine whether they have a decisional or post-decisional origin.…”
Section: Discussionmentioning
confidence: 99%
“…This null result was corroborated by Bayesian analyses supporting the null hypothesis. The role of sensorimotor processing for perceptual monitoring has been a topic of resent research, notably with studies showing a role of motor actions for confidence (e.g., Siedlecka, Paulewicz, & Wierzchoń 2016; Gadjos et al, 2018; Faivre et al, 2018; Pereira et al, 2018). The present study is the first pointing at the specificity of trunk-related signals and bodily-self consciousness for perceptual monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond behaviour alone, Gajdos et al (2019) showed that confidence increases in the presence of sub-threshold motor activity prior to first-order responses. Plus, we recently showed that alpha-desynchronization prior to first-order response (an electrophysiological signature of motor preparation) correlates with confidence over different perceptual tasks (Faivre et al, 2017), that metacognitive performance for decisions that are committed with a keypress is better than that to equivalent decisions that are observed (Pereira et al, 2018), and that sensorimotor conflicts alter confidence (Faivre et al, 2019). Finally, transcranial magnetic stimulation (TMS) directed at the premotor cortex involved in the first-order response was found to affect confidence ratings, suggesting a causal role of action-related signals for confidence (Fleming et al, 2015).…”
Section: Introductionmentioning
confidence: 99%